Quercetina modula a sinalização do cálcio intracelular no coração - Santos, Michel Santana (2016)
Quercetin is a flavonoid widely distributed in plants, and it is shown to have several biological activities. This study aims to describe the effects of quercetin on the contracting and electrophysiological properties of the cardiac muscle as well as the homeostasis of intracellular calcium. This study evaluated the inotropic effect of quercetin in guinea pigs’ left atria, its effects on the adrenergic receptors, and on the electrocardiographic parameters. In mice ventricular cardiomyocytes the L-type Ca2+ current (ICa,L), the intracellular Ca2+ global transient and the calcium sparks were evaluated. The results revealed a positive inotropic effect from quercetin (EC50 3.64 x 10-6 M, n = 4) that was significantly reduced by 1 M propranolol. Furthermore, quercetin caused diastolic relaxation (~7%). In ventricular cardiomyocytes, 30 μM quercetin increased the density of ICa,L at 0 mV of −0.95 ± 0.01 A/F from −1.21 ± 0.08 A/F (n = 5, p < 0.05) and membrane potential at which 50% of the channels are activated (V0.5) diminished to -13.06 ± 1.52 mV from -19.26 ± 1.72 mV (n = 5, p < 0.001) not altering the slope factor. Furthermore, cardiomyocytes exposure at 30 μM quercetin presented [Ca2+]i transient of 4.61± 0.22 (n = 91 cells, p < 0.001) that was 28% higher compared with control situation (3.60 ± 0.14, n = 40 cells). Quercetin also accelerated the [Ca2+]i transient decay kinetics at 90% (t90) from 875.8 ± 13.44 ms to 740.0 ± 26.74 ms (p < 0.001) and at 50% (t50) from 253.3 ± 7.75 ms to 181.4 ± 12.67 ms (p < 0.001). In cardiomyocytes not electrically stimulated, quercetin did not increase the frequency of calcium sparks. In isolated guinea pig heart, quercetin increased the heart rate from 133.1 ± 5.49 bpm to 146.2 bpm ± 5.28 (n = 5, p <0.0001); decreased the PR interval from 107.3 ± 4.69 ms to 100.3 ± 1.79 ms (n = 5, p < 0.05) and decreased the QTc from 10.49 ± 0.048 ms to 10.23 ± 0.06 ms. The duration of the QRS complex was not significantly changed, and there was also no evidence of the appearance of cardiac arrhythmias. Thus, we showed that quercetin activates β-adrenergic receptors, leading to increased L-type calcium current and intracellular calcium transient, not inducing the increase of calcium sparks or arrhythmogenic effects.